(untitled) (Global Journal of Science Frontier Research, 2012)
The derivatives of Indole show biological activities including herbicidal. The newly synthesized compounds 1-phenylethyl,2-methyl,3-ethoxy carbonyl,5-methoxycarbonyl ,2methoxy Indole (Compound 2) were prepared by treating 1-phenyl,3-ethoxycarbonyl,5hydroxy,2-methyl Indole (Com-pound 1) successively with methyl bromo-acetate and refluxing with K2CO3 / KI in the presence of dry acetone. Newly synthesized compound 2 refluxed with hydrazine hydrate in alcoholic media forming 1-Phenylethyl,3-ethoxy carbonyl,2-methyl Indole,5yl oxy acetic acid hydrizide (Compound 3). This drug which on separately reacting with carbon disulphide, phenyl iso-thiocynide, acetylacetone, triethylorthoformate gave condensed bridge head heterocyclic’s such as 1-Phenyl ethyl,2-methyl,3-ethoxy cabonyl,5(5′-mercapto,1′-3′-4’oxadiazol,2′-yl )-methoxy Indole (Compound 4).